A Simple SERS-Based Trace Sensing Platform Enabled by AuNPs-Analyte/AuNPs Double-Decker Structure on Wax-Coated Hydrophobic Surface - Wu, Huixiang; Luo, Yi; Huang, Yikun; Dong, Qiuchen; Hou, Changjun; Huo, Danqun; Zhao, Jing; Lei, Yu (Frontiers in Chemistry, 2018)
In this work, a simple and versatile SERS sensing platform enabled by AuNPs-analyte/AuNPs double-decker structure on wax-coated hydrophobic surface was developed using a portable Raman spectrometer. Wax-coated silicon wafer served as a hydrophobic surface to induce both aggregation and concentration of aqueous phase AuNPs mixed with analyte of interest. After drying, another layer of AuNPs was drop-cast onto the layer of AuNPs-analyte on the substrate to form double-decker structure, thus introducing more “hot spots” to further enhance the Raman signal. To validate the sensing platform, methyl parathion (pesticide) and melamine (a nitrogen-enrich compound illegally added to food products to increase their apparent protein content) were employed as two model compounds for trace sensing demonstration. The as-fabricated sensor showed high reproducibility and sensitivity towards both methyl parathion and melamine detection with the limit of detection at the nanomolar and sub-nanomolar concentration level, respectively. In addition, remarkable recoveries for methyl parathion spiked into lake water samples were obtained, while reasonably good recoveries for melamine spiked into milk samples were achieved. These results demonstrate that the as-developed SERS sensing platform holds great promise in detecting trace amount of hazardous chemicals for food safety and environment protection.